Detergent deterrent - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Schistosomiasis (bilharzia), the parasitic disease transmitted by snails, afflicts more than 200 million people living in 76 tropical countries according to WHO estimates. It has now been found that the soapberry plant (Phytolacca dodecandara) can...